PENGARUH GAYA HIDUP BERBELANJA PROMOSI PENJUALAN DAN MOTIVASI BERBELANJA HEDONIS TERHADAP PEMBELIAN TIDAK TERENCANA DI MATAHARI DEPARTEMENT STORE PEJATEN VILLAAGE - Wahyu Kurniawan, - (2019)
This research is a quantitative research that aims to determine the effect of Shopping lifestyle, Sales promotion, and Hedonic shopping motivation to Impulse buying. The population in this study were Consumers who visited Matahari Departement store. The sample size was taken as many as 100 respondents, with a non probability sampling method with a accidental sampling method. Data collection is done through the distribution of questionnaires. The analysis technique used is the method of PLS (Partial Least Square) analysis with SmartPLS3.0 software. The results of this study indicate that (1) Shopping lifestyle has no influence and is not significant to impulse buying.(2) Sales promotion has no influence and is not significant to impulse buying. (3) Hedonic shopping motivation has a positive and significant influence to Impulse buying. Of the three independent variables namely shopping lifestyle,sales promotion and hedonic shopping motivation that provide the largest contribution is the hedonic shopping motivation variable.